Mobile apps: Incubating talent - Cloete, Laurens (Technical Centre for Agricultural and Rural Cooperation, 2010)
The southern African regional mobile application lab, based in Pretoria, will provide training and industry links to develop the skills of mobile apps entrepreneurs.